Using IoT technologies to develop a low-cost smart medicine box - Silva, Danyllo V. da; Gonçalves, Taisa G.; Pires, Paulo F. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Internet of Things (IoT) is a paradigm that has provided improvements for the day-to-day of society. This paradigm has been applied in several domains such as ambient assisted living (AAL), energy, transportation, environmental, urban monitoring, and healthcare. In the healthcare domain, IoT offers many advantages, such as enable continuous health monitoring, improve quality life and comfort, among others. A kind of IoT application in this domain is smart medicine box, a device that provides medicines treatment monitoring of users. It allows health professionals to verify users’ treatment compliance and supports decision-making. Most of the smart medicine box projects found in the literature are still expensive and do not address some characteristics of IoT systems such as scalability, latency, time to response, among others. Taking into account this scenario, this work proposes a low-cost IoT system prototype to support users during their medicines manipulation. The proposal employs edge-computing concept to add intermediate layer improving the communication among devices and services.